2014
DOI: 10.1155/2014/839135
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima Media Thickness as a Marker of Atherosclerosis in Ankylosing Spondylitis

Abstract: Aim. Increased cardiovascular morbidity and mortality have been observed in ankylosing spondylitis because of accelerated atherosclerosis. We measured carotid intima media thickness (CIMT) as a surrogate marker of atherosclerosis in this study. Methods. In this study 37 cases of AS and the same number of matched individuals were recruited. CIMT measurements were done using B-mode ultrasound. Disease activity was assessed using Bath ankylosing spondylitis disease activity index (BASDAI), Bath ankylosing spondyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 25 publications
7
26
0
1
Order By: Relevance
“…IMT, the main variable of arterial hypertrophy, was 0.79 ± 0.22 and 0.80 ± 0.20 in the left CCA versus 0.73 ± 0.16 and 0.75 ± 0.21 in the right CCA for patients and controls, respectively (p = 0.784 for left CCA and 0.421 for right CCA). We retrieved 23 studies evaluating subclinical CVD in AS; 14 of them 11,12,15,18,[20][21][22][23][24][25][26][27][28][29] fulfilled our inclusion criteria. By univariate regression analysis, none of the disease variables, such as duration and activity or anti-TNF treatment, were associated with any of the vascular indices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IMT, the main variable of arterial hypertrophy, was 0.79 ± 0.22 and 0.80 ± 0.20 in the left CCA versus 0.73 ± 0.16 and 0.75 ± 0.21 in the right CCA for patients and controls, respectively (p = 0.784 for left CCA and 0.421 for right CCA). We retrieved 23 studies evaluating subclinical CVD in AS; 14 of them 11,12,15,18,[20][21][22][23][24][25][26][27][28][29] fulfilled our inclusion criteria. By univariate regression analysis, none of the disease variables, such as duration and activity or anti-TNF treatment, were associated with any of the vascular indices.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have focused on the effect of AS disease per se on endothelial dysfunction and the progress of atherosclerosis 7,[10][11][12][13][14][15][16][17][18][19][20]21,22,23,24,25,26,27,28,29 . A metaanalysis performed in such studies published up to 2009 concluded that atherosclerosis was accelerated in patients with AS, as evidenced by significantly greater intima-media thickness (IMT) values compared with controls 9 .…”
mentioning
confidence: 99%
“…This paradox of a seemingly beneficial lipid profile predisposing to accelerated atherosclerosis in rheumatic diseases was also seen previously. 3,[29][30] The mechanism behind it is the ability of chronic inflammation to induce changes in the structural composition of the lipid molecules, making them more atherogenic. 31 The correlation of disease duration with CIMT, found in our study, can be explained by the fact that it is chronic systemic inflammation which is driving atherosclerosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Chronic systemic inflammation is implicated as the driving force behind accelerated atherosclerosis in rheumatic diseases. [4][5] In RA, mortality due to coronary artery disease was found to be higher than general population indicating increased risk of atherosclerosis in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…В несколь-ких сравнительно недавних исследованиях было показано более существенное увеличение толщины КИМ у больных АС по сравнению с сопоставимой по возрасту и полу группой контроля [9].…”
Section: материал и методыunclassified